2013
DOI: 10.1017/s0144686x1300072x
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of receiving social care in later life in England

Abstract: Demographic change and policy changes in social care provision can affect the type of social care support received by older people, whether through informal, formal state or formal paid-for sources. This paper analyses the English Longitudinal Study of Ageing data (wave 4) in order to examine the relationship between demographic and socio-economic characteristics, and the receipt of support from different sources by older people who report difficulty with daily activities. The research outlines three key resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 28 publications
7
80
0
1
Order By: Relevance
“…, Vlachantoni et al . ). The burden of care is usually coped with following a social hierarchy, which has to do with gender, age, socio‐economic level and degree of relationship.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Vlachantoni et al . ). The burden of care is usually coped with following a social hierarchy, which has to do with gender, age, socio‐economic level and degree of relationship.…”
Section: Introductionmentioning
confidence: 97%
“…, Vlachantoni et al . ). Caregivers who do not have appropriate social support nor the suitable nurse training to provide specific care may be at risk to an overburdening with negative consequences on their health and quality of life (Butterworth et al .…”
Section: Introductionmentioning
confidence: 97%
“…This may explain why we find significant income and wealth influences on receipt of publicly subsidised social care, where Vlachantoni et al. () found none. Finally, we have also been able to exploit newly available data on social care collected in wave 6 (2012) of ELSA, which enable us to distinguish better between those who receive publicly subsidised care and those who pay the full cost of care.…”
Section: Discussionmentioning
confidence: 53%
“…Need is the most immediate reason for using social care. The existing studies have consistently confirmed the central role of care needs in driving home care receipt (Blomgren, Martikainen, Martelin, & Koskinen, ; Bolin, Lindgren, & Lundborg, ; Larsson, Thorslund, & Kareholt, ; Murphy, Whelan, & Normand, ; Stoddart, Whitley, Harvey, & Sharp, ; Vlachantoni, Shaw, Evandrou, & Falkingham, ).…”
Section: Determinants Of Care Receipt: a Literature Reviewmentioning
confidence: 86%